Influence of hydrodynamic parameters in plate heat exchangers in ice slurry transport - Milón Guzmán, Juan José (2023)
Ice slurry is applied in different refrigeration and air conditioning systems, and among its main advantages is the ability to store latent heat and be pumpable as chilled water. This fluid can be used for thermal storage instead of chilled water or solid ice because, at certain concentrations, it can be pumped through heat exchangers. For this technology to be widely used, the equipment must be designed with the heat exchange characteristics in mind. In this study, an experimental system was developed to study the parameters that influence heat exchange, using ice slurry in a plate heat exchanger and water as heat load. Several situations with different flow rates and initial fractions of ice in the ice slurry were analyzed. The inlet conditions of the heat load were kept constant, the temperature, pressure drop and flow rate of the ice slurry in the heat exchanger were controlled as a function of the Nusselt, Prandtl and Reynolds coefficients. The results show that the overall heat exchange coefficient increases with increasing initial ice fraction; the cooling capacity of the heat exchanger increases when ice slurry is used as the fluid. For flow rates above 0.16 kg/s and ice fractions above 11%, ice crystals are generated at the outlet of the heat exchanger, due to the higher viscosity of the ice slurry, at approximately 0.003 Pa at the outlet, as the pressure drop increases with increasing initial ice fraction. The results show the thermohydraulic behavior of the ice slurry. Its use shows favorable characteristics in heat exchange.